2012
DOI: 10.2166/wst.2012.411
|View full text |Cite
|
Sign up to set email alerts
|

A horizontal flow biofilm reactor (HFBR) technology for the removal of methane and hydrogen sulphide at low temperatures

Abstract: A novel horizontal flow biofilm reactor (HFBR) has been adapted and tested for its efficiency in treating hydrogen sulphide (H(2)S) and methane (CH(4)) gas. Six pilot-scale HFBR reactors were commissioned, three each treating CH(4) and H(2)S respectively. The reactors were operated at 10 °C, often typical of ambient temperatures in Ireland, and were simultaneously dosed with an air mixture containing the gas in question and with synthetic wastewater (SWW). Three reactors (HFBR 1, 2 and 3), treating an air mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Removal rates for biofilm-based reactors of between 5 and 169 g H2S m -3 [reactor volume] h -1 at residence times of less than 1 min have been reported [1,2,11,12,13,14,15]. Horizontal-Flow Biofilm Reactor (HFBR) technology has previously been used to treat methane-contaminated airstreams [16,17] and were also shown to be capable of H2S removal in a short proof of concept trial [18]. This study investigated H2S removal in HFBRs in more detail than previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Removal rates for biofilm-based reactors of between 5 and 169 g H2S m -3 [reactor volume] h -1 at residence times of less than 1 min have been reported [1,2,11,12,13,14,15]. Horizontal-Flow Biofilm Reactor (HFBR) technology has previously been used to treat methane-contaminated airstreams [16,17] and were also shown to be capable of H2S removal in a short proof of concept trial [18]. This study investigated H2S removal in HFBRs in more detail than previously reported.…”
Section: Introductionmentioning
confidence: 99%